Cold-formed ferritic stainless steel SHS and RHS beams: Testing, modeling and design. (October 2022) - Li, Lianghao; Li, Hai-Ting; Young, Ben
Abstract: Ferritic stainless steel is characterized by its low or even no nickel content and has relatively lower material cost than austenitic and duplex stainless steel. It may offer a viable alternative in structural applications. In this study, a series of four-point bending tests was firstly carried out on cold-formed ferritic stainless steel (CFFSS) square and rectangular hollow sections (SHS and RHS) to investigate the flexural performance of the tubular section beams. A finite element model was then developed for CFFSS tubular beams. The model was shown capable of predicting the flexural behavior of the beams and therefore an extensive parametric study was undertaken to generate more data over larger ranges of key parameters of the CFFSS sections. The experimental and numerical results as well as the available data on CFFSS SHS and RHS beams were employed to assess the slenderness limits as well as to evaluate the moment capacities predicted by various design provisions such as the American Specification, Australian/New Zealand Standard, European Code, direct strength method and continuous strength method for cold-formed stainless steel beams. It is shown that the current design methods provided quite conservative predictions on the moment capacities of the CFFSS flexural members. Reliability analyses were undertaken and appropriate design rules for CFFSS SHS and RHS beams were suggested in this study. Highlights: Beam tests on cold-formed ferritic stainless steel SHS and RHS were conducted. Finite element model was developed and a parametric study of 151 specimens was performed. Codified slenderness limits for sections subjected to bending were examined. Various existing design provisions for members in flexure were also assessed. Modification to the Eurocode (EN 1993-1-4) provision was proposed for cold-formed ferritic stainless steel beams.